AI-based waste mapping for addressing climate-exacerbated flood risk - Knoblauch, Steffen; Szamek, Levi; Chazua, Iddy; Adamu, Benedcto; Maholi, Innocent; Zipf, Alexander (Climate Change AI, 2025)
Climate Change AI - NeurIPS 2025 Accepted Work
Gesehen am 05.02.2026
Keywords: Konferenzschrift